The relationship between the social responsibility and the job performance among physical education professors - Kenioua Mouloud; Krine Nawal (IP Iermakov S.S., 2020)
Background and Study Aim. The study aimed to know the level of social responsibility and job performance among the physical education professors and examine the relationship between the social responsibility and the job performance. Material and Methods. The participants were 29 physical educations professors (male) from Institute of Physical Education and Sport University of Ouargla. The social responsibility and the job performance scales were used as search tools. Data analyses were carried out by means of statistical packet for social sciences (SPSS) 26.00 software program. The Mean, Std. Deviation and Pearson Correlation were used in the main study. In addition, alpha-Cronbach was used in the exploratory study Results. The level of social responsibility and job performance is high among physical education professors, and there is a positive correlation between social responsibility and job performance. Conclusions. Given the importance of the role of social responsibility and job performance and the lack of enough studies in this specialization, it is necessary to conduct more additional studies that would serve knowledge in this specialization.